2016
DOI: 10.18632/oncotarget.12988
|View full text |Cite
|
Sign up to set email alerts
|

Primary mediastinal large B-cell lymphoma: transcriptional regulation by miR-92a through FOXP1 targeting

Abstract: BackgroundPrimary mediastinal large B-cell lymphoma (PMBL) shares pathological features with diffuse large B-cell lymphoma (DLBCL), and molecular features with classical Hodgkin lymphoma (cHL). The miR-17∼92 oncogenic cluster, located at chromosome 13q31, is a region that is amplified in DLBCL.MethodsHere we compared the expression of each member of the miR-17∼92 oncogenic cluster in samples from 40 PMBL patients versus 20 DLBCL and 20 cHL patients, and studied the target genes linked to deregulated miRNA in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Because mdx mice undergo muscle ischemia after muscle contraction, functional improvement of vasculature, including increased blood flow in ischemic conditions, is crucial, in which Antagomir‐92a treatment can be combined with phosphodiesterase‐5 (PDE5) inhibitor therapy . Other studies also demonstrated the oncogenic effects of miR‐92a, including promotion of cancer growth and inhibition of apoptosis via suppression of p21, KLF2, KLF4, p63, DKK3, PTEN, FOXP1, RBM4, and BCL2L11 genes . In particular, DKK3 has been identified as a diagnostic marker and as a therapeutic target for age‐related muscle atrophy, suggesting that upregulation of DKK3 via Antagomir‐92a administration may induce worsened dystrophic phenotype in mdx mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because mdx mice undergo muscle ischemia after muscle contraction, functional improvement of vasculature, including increased blood flow in ischemic conditions, is crucial, in which Antagomir‐92a treatment can be combined with phosphodiesterase‐5 (PDE5) inhibitor therapy . Other studies also demonstrated the oncogenic effects of miR‐92a, including promotion of cancer growth and inhibition of apoptosis via suppression of p21, KLF2, KLF4, p63, DKK3, PTEN, FOXP1, RBM4, and BCL2L11 genes . In particular, DKK3 has been identified as a diagnostic marker and as a therapeutic target for age‐related muscle atrophy, suggesting that upregulation of DKK3 via Antagomir‐92a administration may induce worsened dystrophic phenotype in mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…8 Other studies also demonstrated the oncogenic effects of miR-92a, including promotion of cancer growth and inhibition of apoptosis via suppression of p21, KLF2, KLF4, p63, DKK3, PTEN, FOXP1, RBM4, and BCL2L11 genes. 33,34,[39][40][41][42][43][44] In particular, DKK3 has been identified as a diagnostic marker and as a therapeutic target for age-related muscle atrophy, 25 suggesting that upregulation of DKK3 via Antagomir-92a administration may induce worsened dystrophic phenotype in mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the miRNAs that are downregulated in RB, miR-let-7a, a tumor suppressor, inhibits cellular proliferation and suppresses tumor growth by inhibiting E2F2 in osteosarcoma cells [ 127 ]. miR-92a, a tumor suppressor, regulates primary mediastinal large B-cell lymphoma (PMBL) by targeting FOXP1, known to deliver an oncogenic effect [ 128 ]. miR-216a plays a role in the inhibition of gastric cancer metastasis via targeting JAK2/STAT3-mediated EMT, thereby suggesting its role in tumor suppression and, ultimately, gastric cancer development [ 129 ].…”
Section: Mirna and Their Targets In Retinoblastomamentioning
confidence: 99%
“…Later, Iqbal et al [ 104 ] described an miRNA signature that allowed the distinction between PMLBCL from other DLBCL, including upregulation of miR-193b and miR-365, and underexpression of miR-629, miR-423-5p, and miR-15a. Higher levels of miR-92a were also described as a classifier of PMBLBCL [ 169 ]. Moreover, a recent study by Malpeli et al [ 170 ] showed that the polycistron miR-17–92 cluster, miR-29 family, miR-150, and miR-497 had the highest power of discrimination between B-cell NHL types, though only eight PMLBCL samples were included.…”
Section: Lymphomasmentioning
confidence: 99%